STRATEGI MEMAJUKAN PENDIDIKAN MADRASAH MELALUI KEPEMIMPINAN BERBASIS TEKNOLOGI - Siswadi (STKIP Subang, 2022)
This study aims to analyze strategies for advancing madrasah education through technology-based leadership in the digital era. The background of this research is based on the demands of educational transformation due to the rapid development of information and communication technology, which requires madrasahs to adapt and innovate in both learning processes and educational management. This study employs a qualitative approach using literature review and conceptual analysis of various theories and practices of technology implementation in education. The findings reveal that strategies to advance madrasah education through technology-based leadership are carried out through several key steps: (1) integrating technology into learning in a planned and relevant manner; (2) improving digital competencies of teachers and students; (3) developing technology-based learning innovations such as gamification and Problem-Based Learning; (4) implementing visionary, adaptive, and innovative leadership; and (5) developing systematic digital strategies through stages of analysis, implementation, and continuous evaluation. In conclusion, technology-based leadership plays a crucial role in driving digital transformation in madrasahs. Strategic and sustainable integration of technology can enhance the quality of learning, improve the effectiveness of educational management, and produce graduates who are competent and ready to face the challenges of the digital era. Keywords: technology-based leadership, madrasah education, digital transformation, learning innovation, educational strategy